2014
DOI: 10.1096/fj.13-247585
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of the heterogeneous membrane distribution of sphingomyelin associated with cytokinesis, cell polarity, and sphingolipidosis

Abstract: Sphingomyelin (SM) is a major sphingolipid in mammalian cells and is reported to form specific lipid domains together with cholesterol. However, methods to examine the membrane distribution of SM are limited. We demonstrated in model membranes that fluorescent protein conjugates of 2 specific SM-binding toxins, lysenin (Lys) and equinatoxin II (EqtII), recognize different membrane distributions of SM; Lys exclusively binds clustered SM, whereas EqtII preferentially binds dispersed SM. Freeze-fracture immunoele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
112
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(117 citation statements)
references
References 79 publications
1
112
0
Order By: Relevance
“…The distribution of SM on the plasma membrane has been investigated with a variety of fluorescently labeled pore-forming toxins derived from marine organisms that bind directly to SM (12,13), and we sought to construct a SM biosensor using one of these, equinatoxin II (Eqt), as a scaffold. Eqt is a member of the actinoporin family, a group of small (∼20 kDa), exceptionally stable proteins that are secreted as inactive monomers and undergo conformational changes to oligomerize into a cytotoxic pore in membranes containing SM (14-20) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The distribution of SM on the plasma membrane has been investigated with a variety of fluorescently labeled pore-forming toxins derived from marine organisms that bind directly to SM (12,13), and we sought to construct a SM biosensor using one of these, equinatoxin II (Eqt), as a scaffold. Eqt is a member of the actinoporin family, a group of small (∼20 kDa), exceptionally stable proteins that are secreted as inactive monomers and undergo conformational changes to oligomerize into a cytotoxic pore in membranes containing SM (14-20) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…GFP, mCherry, mKate, Venus or Dronpa) or small organic molecules ( e.g. Alexa Fluor), have proved useful in confocal or super-resolution microscopy analyses [22, 23, 26, 114] (see Table 1). For further general information on lysenin, please see [110, 111, 115].…”
Section: Evaluation Of New Tools and Methods And Importance Of Celmentioning
confidence: 99%
“…Previously, we have shown that the binding of lysenin to SM was inhibited by the presence of glycolipids (Ishitsuka et al, 2004;Makino et al, 2015). To examine the possibility that the low signal of MBP-lysenin in the inner leaflet was due to the high concentration of glycolipids, we studied the distribution of the main glycosphingolipid of RBCs, GM3 (Larson and Samuelsson, 1980).…”
Section: Transbilayer Distribution Of Phospholipids In Membranes Of Hmentioning
confidence: 99%